ON THE LOGIC OF DECREASING CHARGE DEPRECIATION. - Lorig, Arthur N. (The Accounting Review, 1962)
Abstract An interesting concept regarding depreciation was presented by Professor Robert Dixon in his article, "Decreasing Charge Depreciation-a Search for Logic" which appeared in the October, 1960 issue of The Accounting Review. He argued that decreasing charge depreciation is appropriate and straight-line procedure correspondingly inappropriate even if the asset in question produces the same level of service in each period of its life. The argument presented may seem logical, but further thought raises some disturbing questions. It is true that in purchasing a bundle of services, the utilization of which will extend over some years, less should be paid for those which are postponed (i.e., their future value should be discounted to determine their present worth); and the longer the postponement, the less the unit price which should be paid. But does this really warrant following a declining curve depreciation policy? Are the services to be received in subsequent years any less valuable or useful at the time of utilization than those used in the first year? In other words, is there not an increase in the value of the services (reflected in the cost of carrying the investment in future services) as their time for use approaches which would offset the discount? This paper focuses on these questions.